2023
DOI: 10.1186/s11658-023-00439-8
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ blockade after genetic inhibition of PD-1 aggravates skeletal muscle damage and impairs skeletal muscle regeneration

Abstract: Background Innate immune responses play essential roles in skeletal muscle recovery after injury. Programmed cell death protein 1 (PD-1) contributes to skeletal muscle regeneration by promoting macrophage proinflammatory to anti-inflammatory phenotype transition. Interferon (IFN)-γ induces proinflammatory macrophages that appear to hinder myogenesis in vitro. Therefore, we tested the hypothesis that blocking IFN-γ in PD-1 knockout mice may dampen inflammation and promote skeletal muscle regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…PD-1 contributes to skeletal muscle regeneration by facilitating the transition of macrophages from a proinflammatory to an anti-inflammatory phenotype ( 57 ). IFN-γ, on the other hand, stimulates the formation of proinflammatory macrophages, which seem to impede myogenesis in vitro ( 57 ).…”
Section: Immune-mediated Necrotizing Myopathy (Imnm)mentioning
confidence: 99%
See 2 more Smart Citations
“…PD-1 contributes to skeletal muscle regeneration by facilitating the transition of macrophages from a proinflammatory to an anti-inflammatory phenotype ( 57 ). IFN-γ, on the other hand, stimulates the formation of proinflammatory macrophages, which seem to impede myogenesis in vitro ( 57 ).…”
Section: Immune-mediated Necrotizing Myopathy (Imnm)mentioning
confidence: 99%
“…PD-1 contributes to skeletal muscle regeneration by facilitating the transition of macrophages from a proinflammatory to an anti-inflammatory phenotype ( 57 ). IFN-γ, on the other hand, stimulates the formation of proinflammatory macrophages, which seem to impede myogenesis in vitro ( 57 ). However, Zhuang et al ( 57 ) surprisingly revealed that blocking IFN-γ signaling of PD-1 knockout models actually exacerbated inflammation in the injured muscle, impeded muscle regeneration, and intensified muscle fibrosis.…”
Section: Immune-mediated Necrotizing Myopathy (Imnm)mentioning
confidence: 99%
See 1 more Smart Citation